THE ORGANIZATION’S READINESS TO IMPLEMENT CHANGES - M. V. Polevaya (Финансы: теория и практика, 2017)
The article discusses organizational changes and the major theoretical approaches to them. A brief overview of two approaches to organizational change management. The mechanistic, whereby the organization is seen as a machine, operating according to rigid rules; the changes were planned and implemented “from above”; for the calculation of the resistance can be controlled; careful planning and control system, is considered as the success of the changes. The organic approach considers the organization as an open system that is influenced by the external environment; successful innovation is based on understanding, acceptance and participation of employees. Reviewed by the author, the most common today, organizational change, major change issues facing the national organization; the reason why organizations do not achieve success in implementing organizational changes. Presents various factors of readiness of the organization to change, such as organizational factors such as involvement, awareness, support manual, etc.; and the willingness of employees to change, for example, age characteristics, occupation, intellectual status, etc. Presents the results of the conducted research, held in the Pension Fund of Russia in 2016, with the aim of identifying the level of readiness of employees of the Pension Fund to organizational changes in connection with the transfer of functions of administration of insurance contributions from the Pension Fund to the Federal tax service. The methods and technologies that are appropriate to use when developing and implementing changes in organizations, including the resistance of the staff: such as constant, step-by-step information to employees; involvement of employees in decision-making; support staff; personal interviews; negotiations; development of a variety of output programs for retirement; establishing a compensation program for leaving; control of the psychological climate in the collectives; the control of the level of employee engagement; psychological trainings and trainings; counselling activities for psychological and organizational nature, etc.